Changes in Marriage Age Policy: Analysis of Implementation and Its Impact on Underage Marriage - Afri, Wedi; Syukrawati, Syukrawati; Fajri, Yan; Dewi, Erna; Putri, Mirna (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
PG SLOT to the marriage age limit in Indonesia have led to an increase in the number of underage marriages in West Sumatra. The government's goal in changing the marriage age limit is to reduce the number of underage marriages. Precisely that, this study aims to determine the effect of Law No. 16 of 2019 concerning Marriage on underage marriage from 2019-2023 and the efforts of the local religious affairs office in socializing it. This research uses a qualitative method with a case study approach. Data sources were obtained through PG SLOT, interviews and documentation. First, the results showed that after the law was enacted, the number of underage marriages actually increased from five couples (2016-2019) to nine couples who married underage (2019-2023). This shows that despite the new regulation, the practice of early marriage still occurs. Second, the religious affairs office has made efforts to prevent underage marriage such as providing direct guidance to prospective brides who are getting married. Then utilize the services of religious instructors within the West Sumatra religious affairs office. Another way is to use social media such as Facebook and Instagram by posting things related to the impact of underage R4shub.